Testicular atrophy and growth post orchidopexy in pediatric patients: A systematic review - Faisal F. Aljadani; Badr M. Rafi; Leen M. Alghamdi; Mohammed M. Bukhari; Lena M. Afif; Baraa B. Milibari; Jehad H. Habeeballah; Ali A. Almehmadi; Abdullah Mesawa (Journal of Pediatric Surgery Open)
Background: Undescended testis, also known as cryptorchidism, is a common congenital anomaly in male infants. It is defined as unilateral or bilateral absence of testes in the scrotum. Testicular volume changes, testicular atrophy, or growth are well known established outcomes of surgical orchidopexy. Testicular growth is the end-result wanted for the management of undescended testis. Contrastingly, testicular atrophy is an unwanted complication of orchidopexy. This systematic review is conducted with the aim of getting a clearer picture of whether there is a correlation between the timing, surgery type, or technique of the orchidopexy and the testicular volume changes. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). A thorough search was done on several databases with the aim of finding relevant randomized controlled trials. The screening process was conducted using the Rayyan tool. Five randomized controlled trials were included for the data extraction process in our systematic review. Results: The main findings of our systematic review revealed that earlier surgical management results in better testicular growth. Whereas delaying the surgical management did not show good catch-up growth. Both the types of surgeries and types of fixations had no effect on the size of the testis. Regarding laparoscopic techniques, staged laparoscopic traction orchidopexy showed more favorable results. Conclusions: Early surgical fixation is the critical factor in determining testicular volume changes post-surgery. Neither surgery type or technique play a role in yielding positive or negative results.